What does it take to make the team? Analyzing the talent identification process in competitive ice hockey - Lemoyne, J.; Brunelle, J. F.; Huard Pelletier, V.; Glaude-Roy, J.; Trudeau, F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: In ice hockey, off-season evaluation camps are crucial steps in the preparation and training of national teams. Traditionally, such camps allow for a look at the evolution of different components of athletic talent such as 1) physical fitness, 2) technical skills, 3) psychological aspects and 4) performance in a game context. However, little is known about the real contribution of these camps in the team selection process. The objective of this study is to take a look at a talent identification process by analyzing the contribution of each talent determinant in competitive hockey.